Communicating by Catcalling: Power Dynamics and Communicative Motivations in Street Harassment. (July 2021) - DelGreco, Maria; Ebesu Hubbard, Amy S.; Denes, Amanda
To understand the frequencies and communicative motivations of men engaging in street harassment, men's tolerance of sexual harassment, and the relationship between power and street harassment experiences for both men and women using the frameworks of dyadic power theory and feminist theories, we surveyed 348 undergraduate participants at a university in the Pacific United States. Results indicated that men who believe they have lower power than women were the most likely to report engaging in street harassment. Results also indicated a positive relationship between men's reported tolerance for sexual harassment and men's reports of engaging in street harassment.